Comparison of Limb Salvage with Mega Prosthesis Versus Auto Graft Reconstruction after Cryotherapy in Adolescent Patients with Limb Sarcomas. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To compare the functional outcome of limb salvage in adolescent limb sarcomas treated with Mega Prosthesis Versus Auto Graft Reconstruction as assessed with Musculoskeletal Tumor Society(MSTS) rating Scale.Methods: This retrospective Cohort study was conducted in department of Surgical Oncology, Shaukat Khanum Memorial Cancer Hospital and Research Center Lahore. The medical record of all adolescent (11 to 16 years) patients with limb sarcoma who underwent wide local excision and reconstruction with liquid nitrogen treated auto graft or mega prosthesis operated during the time period extending from 15th January 2018 to 15th December 2021 was reviewed. Both modalities of treatments were compared for functional outcome as assessed with MSTS scoring scale at one year with 0 to 100% score and the higher MSTS score indicating better functional outcome.Results: The records of 35 patients were reviewed. Male patients were 26(74.28%) and females were 09(25.71%). The mean age was 15.8±3.6 years. The predominant type of tumor was Osteosarcoma(77.1%,n=27) and the commonest location was distal femur (40 %,n=14) and proximal tibia(40 %,n=14). Mega prosthesis replacement was done in 20(57.14% ) patients while auto graft reconstruction was done in 15(42.85% ) patients. At one year the mean MSTS score was 25± 5.6 (83.33) in patients with mega prosthesis and 20±7.5(66.66%) in auto graft(P